2016
DOI: 10.1007/s00442-016-3645-y
|View full text |Cite
|
Sign up to set email alerts
|

Using a botanical garden to assess factors influencing the colonization of exotic woody plants by phyllophagous insects

Abstract: The adoption of exotic plants by indigenous herbivores in the region of introduction can be influenced by numerous factors. A botanical garden in Western Siberia was used to test various hypotheses on the adaptation of indigenous phyllophagous insects to exotic plants invasions, focusing on two feeding guilds, external leaf chewers and leaf miners. A total of 150 indigenous and exotic woody plant species were surveyed for insect damage, abundance and species richness. First, exotic woody plants were much less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In addition to the 'degree of novelty' of a novel habitat, it is also important to consider its age (hypothesized as the length of time that a nonnative plant has existed in a region), and its geographic extent (analogous to the range size of a nonnative plant). As the range size of an introduced plant increases over time, more potential colonists are likely to encounter it and develop specialized adaptations, potentially generating a positive correlation between the time since arrival of nonnative plant species and insect herbivore species richness (Brändle et al, 2008;Kennedy & Southwood, 1984;Kirichenko & Kenis, 2016). However, the effect of time is not always apparent (Andow & Imura, 1994;Carpenter & Cappuccino, 2005) and may be overshadowed by the effect of range size once a time-richness asymptote is approached (Banerjee, 1981;Kennedy & Southwood, 1984;Strong, 1974;Strong, McCoy, & Rey, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the 'degree of novelty' of a novel habitat, it is also important to consider its age (hypothesized as the length of time that a nonnative plant has existed in a region), and its geographic extent (analogous to the range size of a nonnative plant). As the range size of an introduced plant increases over time, more potential colonists are likely to encounter it and develop specialized adaptations, potentially generating a positive correlation between the time since arrival of nonnative plant species and insect herbivore species richness (Brändle et al, 2008;Kennedy & Southwood, 1984;Kirichenko & Kenis, 2016). However, the effect of time is not always apparent (Andow & Imura, 1994;Carpenter & Cappuccino, 2005) and may be overshadowed by the effect of range size once a time-richness asymptote is approached (Banerjee, 1981;Kennedy & Southwood, 1984;Strong, 1974;Strong, McCoy, & Rey, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…One main problem is that a PRA is normally only conducted once a pest or pathogen is formally described (FAO 2016). Time limitations and logistical issues restrict the ability of researchers to formally describe unknown taxa in sentinel plantings (Roques et al 2015;Vettraino et al 2015;Kirichenko and Kenis 2016). To alleviate this issue taxonomists based in the exporting countries need to be engaged through networking activities.…”
Section: Sentinel Plants Supporting National Plant Protection Organizmentioning
confidence: 99%
“…A sentinel arboretum ( Fig. 3) comprises a broad range of both native and non-native tree species from diverse regions around the world, which can allow testing of various ecological hypotheses on biological invasions, as possible host-shifts, one of the main barriers to establishment of alien plant pests and pathogens, can be examined (Kirichenko et al 2013;Kirichenko and Kenis 2016;Morales-Rodríguez et al 2018). Non-native species are exposed to inoculum of native, potentially pathogenic organisms harboured by native trees species growing in the same or nearby environment.…”
Section: Sentinel Arboretummentioning
confidence: 99%
“…Several studies have found that the degree of relatedness of co-occurring introduced and native plants is correlated with the amount of damage the introduced plant suffers from native herbivorous insect species (i.e. Bush, 1969;Connor, Faeth, Simberloff, & Opler, 1980;Kirichenko & Kenis, 2016;Pearse & Hipp, 2014;Strong, 1979).…”
Section: Regional Scalementioning
confidence: 99%